Eco-Friendly Synthesis and Characterization of Mg0.5Co0.5Fe2O4 Magnetic Nanoparticles for Photocatalytic Degradation of Congo Red Dye - Dhekra Ahmed Hasan Harki; Ali Naghipour; Saeid Taghavi Fardood (Case Studies in Chemical and Environmental Engineering)
Mg0.5Co0.5Fe₂O4 magnetic nanoparticles were synthesized using a green technique with the assistance of tragacanth gel. The synthesized Mg0.5Co0.5Fe₂O4 MNPs were characterized by XRD, FESEM-EDS, TEM, UV–Vis-DRS, BET and VSM analysis. The XRD confirmed the cubic spinel crystal structure of the nanoparticles. The FESEM and TEM images exhibited a spherical form, with an average particle size of 20–25 nm. The Mg₀.₅Co₀.₅Fe₂O₄ MNPs degraded 93 % of Congo red dye within 30 min under visible light. The sample could be easily reused for five cycles with minimal activity loss. LC-MASS analysis identified the degradation by-products, providing insights into the dye breakdown.